Decision‐Driven Product Development. Issue 2 (21st August 2019) - Hause, Matthew; Korff, Andreas
ABSTRACT: Product line engineering (PLE) is the engineering and management of a group of related products using a shared set of assets and a means of design and manufacturing. PLE can include systems, software, and assets and involves all aspects of engineering including electrical, electronic, mechanical, and chemical, just to name a few. Engineers normally consider PLE after the product has evolved and complexity becomes too much to manage. Leveraging PLE from the very beginning will identify cost savings and commonality and provide a natural means for product evolution. Orthogonal variability modeling (OVM) provides a natural decision set allowing engineers to perform trade‐offs for specific customers and guide system development along the most effective route. Using automotive examples, this paper will describe model‐based product line engineering (MB‐PLE), the process for creating product lines, and the benefits of this approach as applicable to the military ground vehicle domain. Finally, it will show how the adoption of MB‐PLE early in the development life cycle provides more benefits without the potential disruption and reengineering that can occur when engineers adopt it later in the life cycle.